Multichromophoric sugar for fluorescence photoswitching - Maisonneuve, Stéphane; Métivier, Rémi; Yu, Pei; Nakatani, Keitaro; Xie, Juan (Beilstein Journal of Organic Chemistry, 2014)
A multichromophoric glucopyranoside 2 bearing three dicyanomethylenepyran (DCM) fluorophores and one diarylethene (DAE) photochrome has been prepared by Cu(I)-catalyzed alkyne–azide cycloaddition reaction. The fluorescence of 2 was switched off upon UV irradiation, in proportion with the open to closed form (OF to CF) conversion extent of the DAE moiety. A nearly 100% Förster-type resonance energy transfer (FRET) from all three DCM moieties to a single DAE (in its CF) moiety was achieved. Upon visible irradiation, the initial fluorescence intensity was recovered. The observed photoswiching is reversible, with excellent photo resistance.
Keywords: click chemistry; energy transfer; fluorophore; monosaccharide; photochromism